Report from the National Academic Conference »Prawdziwa wolność jest pierwszą cechą człowieczeństwa« (17–18 October 2024, Toruń, Poland) - Skrzypiński, Piotr (Institute of National Remembrance Review, 2025)
Report from the conference entitled »Prawdziwa wolność jest pierwszą cechą człowieczeństwa« – różne wymiary wolności od lat siedemdziesiątych XX wieku do chwili obecnej. Ogólnopolska konferencja naukowa w 40. rocznicę śmierci błogosławionego ks. Jerzego Popiełuszki [“True Freedom is the First Characteristic of Humanity” – various dimensions of freedom from the 1970s to the present day. All-Poland academic conference in fortieth anniversary of Fr. Jerzy Popiełuszko’s death] held on 17–18 October 2024 in Toruń, Poland, organised by Centrum Badania Historii Solidarności i Oporu Społecznego w PRL [Centre for Research on Solidarity History and Social Resistance in Polish People’s Republic] of the Nicolaus Copernicus University and Kujawsko-Pomorski Urząd Marszałkowski (Cujavia-Pomerania Voivodeship Marshal Office).